LOW BACK PAIN IN NURSES AT MULIA HOSPITAL BOGOR - Yenni, Yenni; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Low Back Pain is a musculoskeletal disorder that nurses experience more than other professional workers. This study aimed to analyze the factors associated with symptoms of LBP in nurses at Mulia Hospital, Bogor. The method of this study is an observational quantitative analytic with a cross-sectional design. The study included 57 nurses at the Mulia Hospital with a questionnaire instrument in May-June 2022. Data were analyzed descriptively to provide an overview of LBP in nurses. The results showed that 15 respondents (26,32%) had complaints of LBP. The percentage of nurses with work positions that are not ergonomic or at risk of complaining of LBP is 22 81%, and the percentage of nurses with an ergonomic work position and complaining of LBP is 3,51%. Most complaints of LBP are from nurses with non-ergonomic work positions. It is necessary to have an ergonomic work attitude and stretching exercises to prevent LBP.